Addressing harmful and unequal gender norms in early adolescence. (April 2018) - Chandra-Mouli, Venkatraman; Plesons, Marina; Amin, Avni
Early adolescence (age 10–14) is an important window of opportunity to address gender socialization as the basis for health and social justice. This Comment explains why this is the case and provides illustrative examples of existing evidence on strategies to promote gender equitable attitudes in young adolescents.